Forest Growth Responses to Drought at Short- and Long-Term Scales in Spain: Squeezing the Stress Memory from Tree Rings - Julio Camarero, J.; Gazol, Antonio; Sangüesa-Barreda, Gabriel; Cantero, Alejandro; Sánchez-Salguero, Raúl; Sánchez-Miranda, Angela; Granda, Elena; Serra-Maluquer, Xavier; Ibáñez, Ricardo (Frontiers in Ecology and Evolution, 2018)
Drought-triggered declines in forest productivity and associated die-off events have increased considerably due to climate warming in the last decades. There is an increasing interest in quantifying the resilience capacity of forests against climate warming and drought to uncover how different stands and tree species will resist and recover after more frequent and intense droughts. Trees form annual growth rings that represent an accurate record of how forest growth responded to past droughts. Here we use dendrochronology to quantify the radial growth of different forests subjected to contrasting climatic conditions in Spain during the last half century. Particularly, we considered four climatically contrasting areas where dominant forests showed clear signs of drought-induced dieback. Studied forests included wet sites dominated by silver fir (Abies alba) in the Pyrenees and beech (Fagus sylvatica) stands in northern Spain, and drought-prone sites dominated by Scots pine (Pinus sylvestris) in eastern Spain and black pine (Pinus nigra) in the semi-arid south-eastern Spain. We quantified the growth reduction caused by different droughts and assessed the short-and long-term resilience capacity of declining vs. non-declining trees in each forest. In all cases, drought induced a marked growth reduction regardless tree vigor. However, the capacity to recover after drought (resilience) at short- and long-term scales varied greatly between declining and non-declining individuals. In the case of beech and silver fir, non-declining individuals presented greater growth rates and capacity to recover after drought than declining individuals. For Scots pine, the resilience to drought was found to be lower in recent years regardless the tree vigor, but the growth reduction caused by successive droughts was more pronounced in declining than in non-declining individuals. In the black pine forest an extreme drought induced a marked growth reduction in declining individuals when accounting for age effects on growth rates. We demonstrate the potential of tree ring data to record short- and long-term impacts of drought on forest growth and to quantify the resilience capacity of trees.